Kyai Hegemony as Proxy Marriage Guardians within Madurese ‘Urf Tradition - Warda Tasya Putri; Suwandi Suwandi; Burhanuddin Susamto (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: The Madurese community places the kyai at the center of its religious and social structure, viewing them as authoritative figures whose influence extends into key life rituals such as marriage. Specific Background: In many cases, families in Madura appoint kyai as proxy guardians (wakil wali nikah), despite legal guardianship traditionally belonging to male relatives by lineage. This practice is deeply rooted in cultural and religious reverence. Knowledge Gap: However, limited scholarly attention has been paid to how this custom aligns with Islamic jurisprudence and local tradition (‘urf) within the framework of social hegemony. Aims: This study aims to analyze the kyai’s hegemonic role as proxy guardians of marriage from the perspective of ‘urf, examining how this practice gains legitimacy both socially and theologically. Results: The findings reveal that the appointment of kyai as marriage guardians is a form of voluntary hegemony grounded in communal trust and cultural continuity, deemed valid under Islamic law as long as it does not contradict Sharia principles and receives the consent of the biological guardian. Novelty: This research uniquely integrates Gramsci’s theory of hegemony with Islamic legal concepts to interpret a localized religious practice. Implications: It highlights the dynamic adaptability of Islamic law within indigenous traditions, illustrating the harmonious coexistence between ‘urf and Sharia in sustaining socio-religious cohesion in Madura. Highlights: The kyai holds religious and social authority legitimized by community trust. The practice of appointing kyai as marriage guardians aligns with valid ‘urf in Islamic law. Reflects harmonious integration of Islamic principles with Madurese cultural traditions. Keywords: Kyai, Marriage Guardian, ‘Urf, Hegemony